Gendered communication: Gender mainstreaming and gender differences in the age of gender equality - Wuri Handayani (Universitas Negeri Yogyakarta, 2023)
The implementation of Gender Mainstreaming (Pengarusutamaan Gender, PUG) policies in Indonesia has had a problematic impact on the advancement of women's resources. This is due to a discrepancy between the value system from the West (secular) which is the essence of PUG policy and the value system in Indonesian society. This study was conducted to provide an explanation of the impact of PUG policy implementation in producing a transformation of women's gender identities and roles that are becoming more modern towards the phenomenon of gender communication. This study uses critical discourse analysis from Van Dijk which includes 3 (three) dimensions, namely discourse, cognition, and society, with a micro-macro and power analysis approach. This study found that there is a potential for abuse of power in the interpersonal communication practices of men and women. There are 3 things that become factors: the structure of the mind, the structure of the text (conversation), and the meaning of the message. The operation of gender differences in gender communication practices is supported by sources of legitimacy of cultural belief systems and interpretations of religious teachings. Understanding gender differences and how they operate is beneficial in equal and comfortable communication practices. Gender intelligence will form subjectivity based on the meaning of the coherence or togetherness of the relation pair.